Eksistensi Pidana Kerja Sosial dalam Perspektif Hukum Progresif - Jody Imam Rafsanjani; Rizki Bagus Prasetio; Zaihan Harmaen Anggayudha (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The most current Indonesian Criminal Code (KUHP) contains the concept of Community Service Punishment, which is considered an effort to reform the criminal law system. Community Service Punishment, as a form of punishment in this country, requires an appropriate mechanism to achieve sentencing goals, namely the rehabilitation of convicts through participation in social activities that benefit society. This study aims to analyze the existence of Community Service Punishment to strengthen law enforcers’ understanding of it as one of the main recognized forms of punishment. By using a progressive legal perspective, this research recognizes that the law should consider the development of society and emphasizes the importance of legal reform, if necessary. This study uses a normative juridical approach and conducts qualitative analysis. Based on the results of research conducted through literature studies, it was found that the criminal justice process results in overcapacity in Correctional Facilities, which ultimately hinders the achievement of sentencing goals. Therefore, the importance of imposing Community Service Punishment is very relevant. However, to carry out Community Service Punishment effectively, an organized and systematic procedure is required. This will ensure that the implementation of Community Service Punishment aligns with the expectations and goals to be achieved. We suggest that the relevant parties take advantage of the ratification of the Criminal Code as an opportunity to renew criminal law in Indonesia by increasing the competence and coordination of the criminal justice subsystem in terms of Community Service Punishment.